BATU AKIK MODEL KLAWING GERAKAN LITERASI SEKOLAH BERBASIS PARTISIPASI WARGA SEKOLAH - Supriyono Supriyono; Sigit Mangun Wardono (IAIN Purwokerto, 2019)
Literacy movement is a very important activity in the world of education. This is a serious concern in education in Indonesia because based on the research conducted by the Organization for Economic Co-operation and Development (OECD) in 2006-2007 shows that Indonesia was in the second ranks lowest in the aspect of reading competency quality. These concerns trigger issues that need to be addressed, among others: (1) How to foster the participation of school residents in the school literacy movement ?, (2) How does the implementation of Batu Akik Model Klawing in growing literacy habits in students? The solution in order to grow the school community in the literacy movement is determined by the school community, namely committees, principals, teachers, administrative staff, parents / guardians of students, and students according to their respective capacities. The implementation is paying attention to reading habits, reading habits of high school students, the relevance of reading and writing habits, and aspects of reading habits. Batu Akik Model Klawing is an acronym for words (Read and Write, Active, Creative, Innovative, and Cooperative). Klawing is an acronym for words (Group, Exercise, Observe, Time, Instructions, Values, and Games). The role of the school community is very much needed in developing the school literacy movement and these activities especially reading and writing can be developed through the strategy of applying Batu Akik Model Klawing.